Viscosity Behaviour of Substituted Benzo-1,3,6- Thiadiazepines in Different Percentages of Solvents - P. Deohate, Pradip; B. Agrawal, Pratibha; Berad, B.N. (Asian Journal of Chemistry, 2010)
The viscosities and densities of benzo-(4,5-d)-2,7-diphenylimino- 1,3,6-thiadiazepine (I), benzo-( 4,5-d)-2, 7-di-o-tolylimino- 1,3,6-thiadiazepine (II), benzo-(4,5-d)-2,7-di-m-tolylimino- 1,3,6- thiadiazepine (III), benzo-( 4,5-d)-2,7-di-p-tolylimino-1,3,6-thiadiazepine (IV), benzo-(4,5-d)-2,7-di-o-chlorophenyl- imino-1,3,6- thiadiazepine (V), benzo-(4,5-d)-2, 7 -di-p-chlorophenylimino 1,3,6- thiadiazepine (VI), benzo-( 4,5-d)-2, 7-di-t-butyl- imino-1,3,6-thiadiazepine (Vll) in different percentages of acetone-water, ethanolwater and dioxane-water mixtures have been measured. From the data the relative viscosities have been calculated which are used to measure the molecular interactions in the solutions and to study the viscosity behaviour of substituted benzo-1,3,6-thiadiazepines on the basis of the presence of different substituents.